2016
DOI: 10.1111/nph.13837
|View full text |Cite
|
Sign up to set email alerts
|

VAMP721a and VAMP721d are important for pectin dynamics and release of bacteria in soybean nodules

Abstract: SummaryIn root nodules rhizobia enter host cells via infection threads. The release of bacteria to a host cell is possible from cell wall-free regions of the infection thread. We hypothesized that the VAMP721d and VAMP721e exocytotic pathway, identified before in Medicago truncatula, has a role in the local modification of cell wall during the release of rhizobia.To clarify the role of VAMP721d and VAMP721e we used Glycine max, a plant with a determinate type of nodule. The localization of the main polysacchar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 45 publications
2
32
0
3
Order By: Relevance
“…Constructs were prepared using the Gateway cloning system (Invitrogen). The vector pKGW_GGRR_C was used for promoter GUS fusion (Ivanov et al , 2012) and pGmlbc3-pK7WGF2-R (Gavrin et al , 2016) for N-terminal GFP fusions. For yeast expression coding regions with or without stop were recombined into pDR196GW, pAG426GAL_eGFP_ccdB (Addgene; N-terminal GFP fusions) or pAG426GAL_ccdB_eGFP (Addgene; C-terminal GFP fusion).…”
Section: Methodsmentioning
confidence: 99%
“…Constructs were prepared using the Gateway cloning system (Invitrogen). The vector pKGW_GGRR_C was used for promoter GUS fusion (Ivanov et al , 2012) and pGmlbc3-pK7WGF2-R (Gavrin et al , 2016) for N-terminal GFP fusions. For yeast expression coding regions with or without stop were recombined into pDR196GW, pAG426GAL_eGFP_ccdB (Addgene; N-terminal GFP fusions) or pAG426GAL_ccdB_eGFP (Addgene; C-terminal GFP fusion).…”
Section: Methodsmentioning
confidence: 99%
“…For GmYSL7 promoter GUS fusion constructs, a 2 kb genomic fragment immediately upstream of the GmYSL7 coding region was recombined into either pKGW-GGRR (Gavrin et al 2016) or pKGWFS7 (Karimi et al, 2002). The full-length coding sequence of GmYSL7 was recombined into pGmLBC3-pK7GWIWG2 Gateway vector (Gavrin et al 2016) to create a hairpin RNAi vector for silencing the gene.…”
Section: Methodsmentioning
confidence: 99%
“…For GmYSL7 promoter GUS fusion constructs, a 2 kb genomic fragment immediately upstream of the GmYSL7 coding region was recombined into either pKGW-GGRR (Gavrin et al 2016) or pKGWFS7 (Karimi et al, 2002). The full-length coding sequence of GmYSL7 was recombined into pGmLBC3-pK7GWIWG2 Gateway vector (Gavrin et al 2016) to create a hairpin RNAi vector for silencing the gene. N-terminal GFP fusion constructs for GmYSL7 were constructed from the full-length coding sequence recombined into either pGmLBC3-pK7WGF2-R (Gavrin et al 2016) or a modified pK7WGF2 (pGmLBC3-pK7WGF2) where the 35S promoter is replaced by the GmLBC3 promoter.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work showed that MtSYP132A, a symbiotic t-SNARE protein, is required for the maturation of symbiosomes into functional forms (Pan et al, 2016). In soybean (Glycine max), GmVAMP721d, a symbiotic v-SNARE protein, plays an important role for the rhizobial release into infected cells of determinant nodules by delivering host-derived pectin-modifying enzymes to the rhizobial release site (Gavrin et al, 2016). Recent work showed that the synaptotagmins MtSyt1, MtSyt2 and MtSyt3 play important roles in the intracellular accommodation of rhizobia and the formation of the Medicago-rhizobia interface membrane (Gavrin et al, 2017).…”
Section: Introductionmentioning
confidence: 99%